Women entrepreneurs in the ICT-related business in Malaysia: A demographic survey - Fuad, Nurwahida; Bohari, Abdul Manaf; Cheng, Wei Hin (Canadian Center of Science and Education, 2011)
Women entrepreneurs has contribute important roles of business, includes the ICT-related business in Malaysia.Nowadays, women entrepreneurs are an integral part of ICT business which involved in Hand phone Shop, Computer Accessories, Cyber Cafe, Internet Shop, ICT-based Training, Photography Shop, Hardware Suppliers, Kiosk, and many more. Although women entrepreneurs are highlighted as have significance contribution toward the nation, however, research regarding the demographic characteristics of women entrepreneurs is still less.Common issues analyzed in the previous literature include gender and personal characteristics such as education, experience, age, marital status, and so on.This research developed a demographic profile revealing characteristics. of the Malaysian women entrepreneur. This study was conducted among 150 women entrepreneurs in Malaysia that were listed in USAHANITA’s online directory which who are focused on conduct ICT-based business. This analysis highlights the complexity of demographic issues among Malaysia women entrepreneurs. The suggestions of this study are briefly formulated to make the women entrepreneurs more competitive in the current environment of business marketplace.